1999
DOI: 10.1111/j.1745-4530.1999.tb00494.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF DIFFERENT PASTEURIZATION CONDITIONS ON ENZYME INACTIVATION OF ORANGE JUICE IN PILOT‐SCALE EXPERIMENTS1

Abstract: The orange juice pasteurization is associated with enzymatic degradation (primarily pectin‐methylesterase) of soluble pectin. Time‐temperature curves were established to study different pasteurization conditions on enzyme inactivation, for fresh single‐strength orange juice from Florida, containing natural PME enzyme. The orange juice was heated in a DeLaval, model P5‐VRB plate heat exchanger with heating and cooling sections, and a 0.0101 m3 volume holding tube. The temperature in the heat exchanger was contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
4
9
0
2
Order By: Relevance
“…As was observed, neither pasteurisation process affected°Brix, at a range between 9.9-10.1, or pH (2.92-3). Similar results were found by Kim and Tadini (1999), who showed that temperature and holding time had no effect on pH and°Brix of conventional pasteurised juice. These quality parameters are important as they are closely related with the stability of the bioactive compounds in fruit products .…”
Section: Resultssupporting
confidence: 93%
“…As was observed, neither pasteurisation process affected°Brix, at a range between 9.9-10.1, or pH (2.92-3). Similar results were found by Kim and Tadini (1999), who showed that temperature and holding time had no effect on pH and°Brix of conventional pasteurised juice. These quality parameters are important as they are closely related with the stability of the bioactive compounds in fruit products .…”
Section: Resultssupporting
confidence: 93%
“…The SSC ranged between 4.73 and 5.27 °Brix, pH values were 4.11–4.26, and TA had a mean of 0.37% in unheated and heated samples without significant differences (data not shown). The literature reported that temperature and treatment time had no effect on pH and °Brix of CP orange juice …”
Section: Resultsmentioning
confidence: 97%
“…According to Kimball,4 a temperature of 88 °C or more for about 10–15 s is required to inactivate most of the pectic enzyme; however, this condition can reduce ‘freshness’ and affects the sensory and nutritional characteristics of OJ. Thermal inactivation of PME has been the subject of many studies 6–16. Since PME is known to be more heat‐resistant than the common spoilage microorganisms of OJ, inactivation of PME is generally used to determine the intensity of thermal processing during commercial pasteurisation 3, 4, 17…”
Section: Introductionmentioning
confidence: 99%
“…In general, PME heat inactivation is considered to follow first‐order kinetics. Versteeg et al 3 Ülgen and Özilgen20 and Kim et al 13 used this approach to study PME heat inactivation kinetics. Nevertheless, the heat exposure times in these studies were all longer than 30 s (most of them in minutes), when the more heat‐labile isoenzymes are already inactivated.…”
Section: Introductionmentioning
confidence: 99%